Analysis of air quality changes and causes in the Liaoning region from 2017 to 2022 - Wang, Jinhu; Ren, Kejin; Su, Hang; Zhou, Chunxiao; Li, Xiaolan; Wang, Yuhao (Frontiers in Environmental Science, 2024)
Using the air quality monitoring data from the Department of Ecology and Environment of Liaoning Province for the period from 2017 to 2022, the temporal and spatial changes in the concentrations of various air pollutants in the Liaoning region for the periods from 2017 to 2019 and 2020 to 2022 were analyzed by using the Evaluation on the meteorological condition index of PM2.5 pollution (EMI) and the ArcGIS Kriging Interpolation Method, and the contributions of pollution reduction to the changes in the air quality of the Liaoning region were assessed. The results show that after the implementation of emission reduction measures, the quality of the atmospheric environment in the Liaoning region has significantly improved, and the mean concentrations of PM2.5, PM10, SO2, NO2, CO and O3 are all reduced by a certain magnitude in the period 2020 to 2022 compared with the period 2017 to 2019; Based on the EMI index calculation, the average EMI index in Liaoning during the period 2020 to 2022 is about 1.7% lower than the average value of the region during the period 2017 to 2019, and the atmospheric dispersion conditions are relatively good; From the perspective of daily changes in pollutant concentrations, the trend of PM2.5 and PM10 concentrations changed from double peaks and single valleys to single peaks and single valleys, and there were no significant changes in the types of valleys for CO, SO2, NO2, and O3, whereas the peaks of O3 concentrations during the daytime were basically the same as in previous years, and the concentrations during the nighttime were slightly higher than in previous years. Classification by topographic areas revealed that the mean pollutant concentration for the period from 2017 to 2019 was more significant than the mean value for the period from 2020 to 2022, except for O3, where the air quality in the mountainous areas of Liaodong and Liaoxi was better than that of the Liaohe Plain, and regional classification by coastal and inland, where the air quality in the coastal areas was better than that of the inland areas.